A 5-year Evaluation of the Publications Made in the Field of Dermatology in Turkey - SALMAN, ANDAÇ (GALENOS YAYINCILIK, 2018)
Objective: Retrospective evaluation of scientific productivity is a guideline for the development of future studies in the planning and quality aspects. There is only one study evaluating the scientific productivity of our country in the field of dermatology. For this reason, in this study, it was aimed to evaluate from the point of quantity and quality of dermatology publications made in our country between 2012-2016 years. Methods: All publications, registered in Index Medicus between January 1, 2012 and December 31, 2016 were searched using the keywords dermatology, Turkey and evaluated accordingly years, topics and publication type. Web of Science database was used to evaluate citation numbers. Results: The total number of publications, research and other publication types made in the field of dermatology in our country increased every year during the dates covered by the study. However, it was observed that the rate of original research among all publications did not increase at the same rate, the number of citations per publication was low compared to other countries, and the number of publications in journals with high impact factor was very low. Conclusion: In addition to the quantitative improvement of publications in the field of dermatology in our country, plans should be made to improve them also in terms of quality.
Keywords: Research; bibliometrics; scientific productivity; dermatology; Turkey; publications; BIBLIOMETRIC ANALYSIS; PRODUCTIVITY; COUNTRIES; JOURNALS; TRENDS